Pengaruh Penggembalaan Pendeta terhadap Kedisiplinan Siswa di Sekolah Kristen Berdasarkan Amsal 22:15 - Sabat Sabat; Milton T. Pardosi (Departement of Mathematics Education, 2023)
Being a Christian School Chaplain is a very influential position in the world of educational services in Christian schools. As a chaplain, you have many roles because you help the church to grow and develop both in spiritual and physical life. Therefore, the role of a chaplain in the life of the ministry both in the congregation and at school is very important. Therefore, the pastor must prepare well and also organize all things related to the pastoral service where he serves. A pastor not only prepares himself to serve in the pulpit, but a pastor also prepares himself to be a teacher. Because being a pastor is not only being a preacher, but also teaching, being a teacher for the congregation and for students while in school and can be exemplified.